Strengthening Religious Moderation Values among Children in Babakanmulya Village, Cigugur Sub-District, Kuningan Regency through Traditional Dance - Balgis Bachmisd; Diana Putri Alam; Farah Zaida; Ghazi Muhammad Tsany; Mohammad Amirudin; Uu Nurul Huda (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2024)
The construction of religious moderation in children through dance in Babakan Mulya is a strategic initiative to strengthen moderate attitudes in a pluralistic society. Implemented by KKN Religious Moderation IV students using the Sisdamas approach, the program involved four cycles: initial socialization, social mapping, participatory planning, and program implementation and evaluation. Survey results revealed misconceptions about local arts being tied to specific religions. The program addressed this by promoting tolerance and diversity through cultural activities, such as dance group formation. Local teenagers trained the children in dance, enhancing interfaith and ethnic relations. The program ended with an evaluation showing increased understanding among children about respecting diversity and maintaining harmony. The final results indicated that children began to appreciate cultural and religious diversity, contributing to a more moderate and harmonious society in the future.